Drug Repurposing for Age-Related Macular Degeneration (AMD) Based on Gene Co-Expression Network Analysis - Samadi, Sina; Ghalandari, Zahra; MotieGhader, Habib; Maleki, Masoud; Yari, AmirHosseinYari; Rezapour, Ali (Journal of Ophthalmic and Optometric Sciences, 2020)
Background: Age-related macular degeneration (AMD) is a lesser-known eye disease in the world that gradually destroys a person’s vision by creating dark spots in the center of vision. Material and Methods: Samples of AMD-related genes were extracted from the NCBI, then the gene expression network (GCN) was extracted. In addition, pathway enrichment analysis was performed to investigate the role of co-expressed genes in AMD. Finally, the drug-gene interaction network was plotted. Results: The results of this work based on bioinformatics showed that many genes are involved in AMD disease, the most important of which are the genes of TYROBP, LILRB2, LCP2, PTPRC, CFH, SPARC, HTR5A. Overexpression of these genes can be considered as basic biomarkers for this disease, we separated some of which we had from the gene co-expression network and some from the results of genes ontology (genes that have a P value ≤ 0.05). The most important drugs were isolated from the drug-gene network based on degree, which included 5 drugs including ocriplasmin, collagenase clostridium histolyticum, topiramate, primidone, butalbital. Conclusion: Among the genes we found, three genes of CFH, TYROBP, SPARC seem to be more important than the others. Among drugs, ocriplasmin, topiramate, primidone can play a more important role based on the degree in the drug-gene network, because all steps are performed with different bioinformatics methods, clinical trials must confirm or reject the results. Keywords: Age-Related Macular Degeneration; AMD; Co-Expression Network; Drug Repurposing.